How Can Pelvic MRI with Diffusion-Weighted Imaging Help My Pregnant Patient? - Horowitz, Jeanne M.; Hotalen, Irene M.; Miller, Emily S.; Barber, Emma L.; Shahabi, Shohreh; Miller, Frank H. (American Journal of Perinatology, 2020)
The purpose of this review is to explain how diffusion-weighted imaging (DWI) is used during magnetic resonance imaging (MRI) exams in pregnant patients for specific maternal indications, including evaluation of acute pelvic pain, adnexal masses, cancer diagnosis and staging, and morbidly adherent placenta. While ultrasound is often the appropriate initial imaging for evaluating a pregnant patient, MRI can be helpful when a pelvic ultrasound is indeterminate. MRI has advantages in that it does not use ionizing radiation and has shown no known deleterious effects to the fetus. The use of gadolinium-based contrast is controversial during pregnancy. DWI is a functional sequence performed during an MRI exam, which is valuable in the absence of gadolinium contrast, and can increase the visibility of inflammation, abscesses, and tumors. Case examples will be presented to demonstrate the utility and added value of DWI over conventional anatomic T1- and T2-weighted imaging in diagnosis of maternal disease in the pregnant patient's pelvis.
Keywords: magnetic resonance imaging; diffusion-weighted imaging; pregnancy; pelvic pain; adnexal mass; cancer; placenta